PERSEPSI MAHASISWA DAN DOSEN PADA PEMBELAJARAN INTERPROFESSIONAL EDUCATION (IPE) DI PRODI D-III AKUPUNKTUR JURUSAN AKUPUNKTUR POLITEKNIK KESEHATAN KEMENKES SURAKARTA - Maria Dewi Christiyawati; Saka Suminar (KOSALA : Jurnal Ilmu Kesehatan, 2017)
Background : IPE is an implementation of learning that is followed by two or moredifferent professions to improve collaboration and quality of service which can be done inall learning, whether it is for undergraduate students or students of educataion clinic tocreate a professional health care personnel. The lack of IPE developer in Indonesia givesanew breakthrough for Health Polytechnic of Minister of Healt Surakarta to begin theinitial steps introducing the IPE learning process to all students.Methods : cross section with spreading the perception questionnaire aboutInterprofessional Education (modification of the IEPS) to students and faculty at D-IIIAcupuncture Study Program Acupuncture Health Polytechnic Department of Minister ofHealths of Surakarta. Total sampling taken with the number of 53 respondents. Data wereanalyzed using Regressoni Logistik Biner.Results show, it can be concluded that the student perceptions of instructional IPE in D-IIIstatus of Acupuncture, Acupuncture Health Polytechnic Department of Minister of Healthof Surakarta who are 36 people (92.31%) gave a good perception, and 3 people (7,69%)gave a average perception.Perceptin lecture of D-III Acupuncture study program,Acupuncture Health Polytechnic Department of Minister of Health of Surakarta who are12 people (85.7%) gave a good perception and 2 people (14,3%) gave averageperception.Keywords: Interprofessional Education (IPE), perception, students and lecturer